2014
DOI: 10.1007/s00213-014-3503-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of blue light and caffeine on mood

Abstract: The benefits of the combination of blue light and caffeine should be further investigated across a range of applications due to the observed effects on the dimensions of arousal, valence and pleasant activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 62 publications
2
17
0
Order By: Relevance
“…As noted in the introduction, there is a growing literature on the beneficial effects of blue enriched light exposure on alertness and cognition [17,[19][20][21][22]. Previous research has found that blue light improves alertness and the present study also found that workers in the EC buildings reported significantly less drowsiness and greater alertness, and this may be because of the blue light that is transmitted through the EC even in its darkest tint state.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…As noted in the introduction, there is a growing literature on the beneficial effects of blue enriched light exposure on alertness and cognition [17,[19][20][21][22]. Previous research has found that blue light improves alertness and the present study also found that workers in the EC buildings reported significantly less drowsiness and greater alertness, and this may be because of the blue light that is transmitted through the EC even in its darkest tint state.…”
Section: Discussionsupporting
confidence: 65%
“…Mills, Tomkins, and Schlangen [17] found significantly less fatigue and daytime sleepiness, improved alertness and work performance, greater vitality and better mental health in a shift-working call center with high correlated color temperature (17000 K) fluorescent lights with greater blue light wavelengths that can stimulate ipRGCs. There is a growing body of evidence that blue light can improve mood, alertness, memory, cognitive performance and aids in coping with any effect of a post-lunch dip on the EEG and in performance [18][19][20][21][22][23]. Hedge and Nou [24] found that electrochromic glass also may improve worker visual comfort and satisfaction, and reduce symptoms associated with CVS.…”
Section: Introductionmentioning
confidence: 99%
“…Such effects include potential positive cognitive enhancement (18), increased alertness (19), and antidepressive effects (20) of blue light; these effects are counterbalanced by the negative effects of this portion of the spectrum when presented in the evening. Further study of these phenomena will be essential for informed policy on questions such as appropriate spectra of LED-based lighting and computer monitors.…”
mentioning
confidence: 99%
“…One possibility is the higher amounts of shorter wave blue light in the early part of the day [ 242 ]. Given the emerging research on appropriately timed blue light exposure and positive mental health [ 243 ], it appears to be yet another feature of the total modern environment that we may be missing, at least in the daytime. While our standard interior lighting cannot compensate for the amount of blue light found in natural daylight [ 244 ], only a small amount of evening blue light can suppress melatonin.…”
Section: The Total Environmentmentioning
confidence: 99%
“…This, in turn, may have many health consequences. Lack of natural light and a compromised ability to secure normal circadian rhythms can interact with all of the above [ 243 , 248 , 293 - 297 ]. Physical activity, unquestionably of value to human health and well-being, may be more pleasurable in outdoor natural environments, with diminished perceptions of exertion and an increase in the likelihood that an individual will be motivated to engage in further physical activity [ 298 - 302 ].…”
Section: Summary and Future Directionsmentioning
confidence: 99%